Transient Analysis of a Single-Phase Variable Speed Cage Induction Generator with Active Excitation Control - Liyanage, Diana; Rajakaruna, Sumedha (University of Tasmania, 2013)
This paper presents the transient behavior of a recently introduced configuration of a single-phase induction generator (IG) which employs a three-phase squirrel cage induction machine. One of the three windings of the machine is used for excitation control and active power control using a bidirectional power converter. The other two windings connected in series form the generator output to which the load and supplementary excitation capacitor are connected. The dynamic equations of the IG have been developed on actual time based abc reference frame model to simulate the generator performance in MATLAB Simulink. The transient behavior of the IG under both no load condition and loaded condition are analyzed in this paper. The transients at the load changes, the mechanical torque changes and excitation voltage changes are presented in this paper. These simulated results accurately present the expected output of the machine.